Perancangan Database Sistem Reservasi Kamar Hotel Berbasis Web Menggunakan ERD, CDM, PDM - Aisyah Rahma Setiaputri; Alvita Dita Azzahra; Lathisya Sheza Aldamar; Zatin Niqotaini (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
The development of information technology has encouraged digitalization in various sectors, including hospitality. However, many hotels still manage room reservation data manually, making them prone to recording errors and slow service. This research aims to design a structured webbased hotel room reservation database system, using the Entity Relationship Diagram (ERD), Conceptual Data Model (CDM), and Physical Data Model (PDM) approaches. The method used follows the Software Development Life Cycle (SDLC) model, starting from requirements analysis, system design, to implementation. The design includes six main entities: Customer, Receptionist, Manager, Room, Reservation, and Payment, which are interconnected through clear relationships. CDM is used to conceptually simplify the data structure, while PDM describes technical aspects such as data types, primary keys, and foreign keys. With a systematic design, it is expected that this system can improve the efficiency of data management, minimize errors, and support hotel operations optimally.